Proportions of Cancer Cases in Primary Care, Hospital, and Cancer Registry Data Among Patients Treated for Overactive Bladder. Issue 2 (March 2019) - Margulis, Andrea V.; Fortuny, Joan; Kaye, James A.; Calingaert, Brian; Reynolds, Maria; Plana, Estel; McQuay, Lisa J; Jan Atsma, Willem; Franks, Billy; de Vogel, Stefan; Perez-Gutthann, Susana; Arana, Alejandro
Abstract : Supplemental Digital Content is available in the text.